Application of Taylor-Newton homotopy method for solving electrical engineering design problem - Hassan, Talib Hashim; Azram, Mohammad; Daoud, Jamal Ibrahim (2009)
We describe simple implementations of homotopy (also called continuation) algorithm for determining the proper resistor to dissipate energy at a specified rate of an electric circuit. Homotopy algorithm can be considered as a developing of the classical methods in numerical computing such as Newton- Raphson and fixed point methods. In homoptopy methods,a n embeddingp arameteris usedt o control the convergenceT. he methodp urposedi n this work utilizes a special homotopy called Newton homotopy. Numerical example solved in MATLAB is given to showt he effectiveness of the purposed method.